Efektivitas Pendekatan Kontekstual, Open-Ended, dan STEM dalam Pengembangan Kemampuan Berpikir Kritis Siswa: Systematic Literature Review - Nurfitriani, Dian Ageng; Subekti, Fitrianto Eko (Proximal: Jurnal Penelitian Matematika dan Pendidikan Matematika, 2024)
Effective learning does not only aim to convey knowledge, but also to develop critical thinking skills that are important for students in facing various life challenges. Critical thinking skills enable students to analyze, evaluate and solve problems logically and independently. This article explores how contextual, open-ended and STEM learning approaches contribute to the development of students' critical thinking skills. Using the Systematic Literature Review (SLR) method, this research collected and evaluated journal articles from the Google Scholar database published between 2019 and 2024, focusing on these three approaches. The results of the analysis show that the contextual approach helps students relate the learning material to real situations, which enhances their understanding and application of knowledge. The open-ended approach encourages students to find multiple solutions and improve their analytical skills, while the STEM approach emphasizes the integration of disciplines to facilitate collaborative and creative learning. These three approaches are proven to be effective in improving students' critical thinking skills, which is reflected in their improved ability to identify, analyze and solve problems. This study provides important insights for educators and researchers to develop more effective learning strategies.